ENTITAS WISATAWAN ASING TERHADAP KEMAMPUAN BERBAHASA INGGRIS MASYARAKAT LOKAL BANJAR TEGAL GUNDUL, DESA TIBUBENENG, KUTA UTARA, BADUNG, BALI: ENTITAS WISATAWAN ASING TERHADAP KEMAMPUAN BERBAHASA INGGRIS MASYARAKAT LOKAL BANJAR TEGAL GUNDUL, DESA TIBUBENENG, KUTA UTARA, BADUNG, BALI - Widani, Ni Nyoman; Suktiningsih, Wiya (LPPM Universitas Bumigora Mataram, 2020)
Abstract Banjar Tegal Gundul as tourist villages in the province of Bali, which visits by foreign and domestic tourists. Every years the number of foreign and domestic tourists to the Banjar Tegal Bald is increases. This situation makes the tourism sector as the main livelihood of local people. That's condition become the background of this research, they are: 1) to understand how to influence tourist entities to the English language skills of local people in Banjal Tegal Gundul and 2) how language attitude of local society towards English. The research uses the method of observation and questionnaire submitted to 24 respondents, who are local people as workers and business owners in the area. This study is found that the language functions used by local people to communicate with foreign tourists is: Greetings, Offering, asking for information, giving information, Saying Like, Giving an opinion, persuading, asking someone to do something, Accepting invitations, apologizing, persuading, and saying / returning thanks. The sentences are used in grammatical rules in English. The language attitudes towards English seen from the cogBanjar Tegal Gundul is one of the tourist villages in the village area of ​​Tibubeneng, North Kuta, Badung, Bali, which receives visits by foreign and domestic tourists. Every year the number of foreign and domestic tourist arrivals to the Banjar Tegal Gundul region has increased. The situation makes the tourism sector as the main livelihood of the local community Banjar Tegal Gundul. The situation is the background of this research, namely: 1) to find out how the influence of foreign tourist entities on the English language ability of local people in Banjar Tegal Gundul and 2) how the attitude of the local people's language towards English. The research uses the method of observation and distributes questionnaires to 24 respondents, who are local people as workers and business owners who are in the area of ​​the area. The step taken in this study is to analyze the language functions used by local people when communicating with foreign tourists. The results obtained in this study indicate that local people are able to communicate with foreign tourists, by using language functions such as: Greeting, Offering, asking for information, giving information, Saying Like, Giving opinion, persuading, asking someone to do something, Accepting invitation, apologizing, persuading, and saying / reply to thank. The sentences are used in accordance with grammatical rules in English. For language attitudes towards English seen from the cognitive, affective and conative components, showing positive language attitudes by local people towards English. That is because the equality of local people's thought orientation will benefit from English, for the livelihoods of local people, both in terms of workers or business owners in the Banjar Tegal Gundul region.